Implementación de una estación retransmisora de radio en FM para una red satelital regional en el Nororiente Peruano - Quispe Rojas, Julio Ernesto (2019)
Commercial broadcasting systems in the mid-twentieth century, were performed using amplitude modulation - AM and the radio signal generated locally to transmit directly to their area of influence. In the second half of the twentieth century, the transmission frequency modulation - FM, it quickly spread about the quality of sound, which is a signal with two channels, left and right, and in the last decade of the twentieth century in our country using satellite links and FM broadcasters, making national radio, and achieved the highest-rated radio listeners in the provinces. The costs for the satellite uplink, you could take if they needed more than a dozen base stations, however with technological development, now is accessible to entrepreneurs and provincial institutions to form regional channels, with signal generated in the main town in the area, with information of local interest and with a program aimed at satisfying the tastes of the region. The project addresses the need to expand coverage and improve signal quality, and obeying the challenge of the transmitted signal reaches the districts of the province and neighboring provinces, and stereo sound quality, using stations FM broadcast, forming a Regional Satellite Network in the Northeast of Peru, in the northern department of Cajamarca and Amazonas, on the border with the neighboring country of Ecuador. The project is aimed to harness satellite system that has the organization, formed by a transmission station to the satellite or Link Up, and only one receiving station and amplitude modulated broadcasting - AM, located in the province of Jaén, Department of Cajamarca. The present article to share the experience has had on the design and implementation of the FM relay station for Regional Satellite Network, implementing the satellite receiving station and FM broadcasting in the District of Chirinos, in the Province San Ignacio, in the Department of Cajamarca.